2022
DOI: 10.23960/jhptt.12233-40
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of arthropod in the various intensity of pesticide applied on shallots crop Local Palu

Abstract: Excessive use of pesticides confers several ecological and environmental consequences. In this research, we evaluated arthropod occurrence on shallot crops in Palu Valley, Central Sulawesi as an impact of pesticide application in different frequencies. Almost all farmers used synthetic pesticides for controlling pests and diseases where 46.7%, 43.3%, 10.0% of them applied in high, moderate, and low frequency, respectively. By comparing to the last application, the first reduced arthropod diversity index, evenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Where, I = Attack intensity, Z = highest score (9), N = number of leaves observed, ni = number of leaves attacked on the i-scale and vi = i-damage scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Where, I = Attack intensity, Z = highest score (9), N = number of leaves observed, ni = number of leaves attacked on the i-scale and vi = i-damage scale.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by the use of chemical insecticides have an impact on predators and also due to the small number of host plants that function as shelter or habitat for insects to lay eggs or find food, while the dominance index and diversity index on the MB treatment (D = 0,52, H' = 2,14) were higher than the farmer treatment because, although it did not use intercropping plants, the control treatment did not use chemical insecticides (Figure 1). If insecticides are applied frequently, the abundance of arthropods drops drastically to a level of 0-1 or decreases from around 94,4% to 100% [9]. This proves that in integrated pest management it is not enough just to use botanical insecticides, it must be accompanied by the use of intercropping, one of which is with cover crops to increase the population and diversity of predators.…”
Section: Insect Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are commonly employed to control Plant Pest Organisms (PPOs) as they are perceived as a guarantee against yield loss due to PPO attacks [4][5][6][7]. However, the government has gradually shifted its pest control policy from a unilateral approach to a comprehensive one, as outlined in Law Number 12 in 1992, further reinforced by Government Regulation Number 6 in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Moekasan et al [3] reported that important pests in shallots are onion caterpillar (Spodoptera exigua), trips (Thrips tabaci) [2], Gryllotalpa sp. [4], anthracnose (Colletotrichum gloeosporioides) [5], fusarium wilt (Fusarium oxysporum) [6], and purple spot or troll (Alternaria porri) [7]. Yield loss due to the pest attack on shallot plants is quite significant, ranging from 24-100%.…”
Section: Introductionmentioning
confidence: 99%